Toxicological, Enzymatic, and Molecular Assessment of the Insecticide Susceptibility Profile of Triatoma infestans (Hemiptera: Reduviidae, Triatominae) Populations From Rural Communities of Santa Cruz, Bolivia. Issue 1 (17th December 2016) - Santo-Orihuela, Pablo L.; Vassena, Claudia V.; Carvajal, Guillermo; Clark, Eva; Menacho, Silvio; Bozo, Ricardo; Gilman, Robert H.; Bern, Caryn; Marcet, Paula L.
Abstract : A wide range of insecticide resistance profiles has been reported across Bolivian domestic and sylvatic populations of Triatoma infestans (Klug, 1834) (Hemiptera, Reduviidae), including some with levels proven to be a threat for vector control. In this work, the insecticide profile of domestic T. infestans was studied with standardized toxicological bioassays, in an area that has not undergone consistent vector control. F1 first-instar nymphs hatched in laboratory from bugs captured in three communities from the Santa Cruz Department were evaluated with different insecticides. Moreover, the enzymatic activity of esterases and cytochrome P450 monooxygenases was measured in individual insects to evaluate the possible mechanism of metabolic resistance to pyrethroids. In addition, the DNA sequence of sodium channel gene (kdr) was screened for two point mutations associated with pyrethroid resistance previously reported in T. infestans . All populations showed reduced susceptibility to deltamethrin and α-cypermethrin, albeit the RR50 values varied significantly among them. Increased P450 monooxygenases and permethrate esterases suggest the contribution, as detoxifying mechanisms, to the observed resistance to deltamethrin in all studied populations. No individuals presented either mutation associated to resistance in the kdr gene. The level of susceptibility to α-cypermethrin, the insecticide used by the local vector control program, falls within an acceptable range to continue its use in these populations. However, the observed RR50 values evidence the possibility of selection for resistance to pyrethroids, especially to deltamethrin. Consequently, the use of pyrethroid insecticides should be closely monitored in these communities, which should be kept under entomological surveillance and sustained interventions.